Preparation of primary standard mixtures for atmospheric oxygen measurements with less than 1 µmol mol−1 uncertainty for oxygen molar fractions - N. Aoki; S. Ishidoya; N. Matsumoto; T. Watanabe; T. Shimosaka; S. Murayama (Atmospheric Measurement Techniques, 2019)
Precise monitoring of changes in atmospheric O2 levels was implemented by preparing primary standard mixtures with less than 1 µmol mol−1 standard uncertainty for O2 molar fractions. In this study, these mixtures were crafted in 10 L high-pressure aluminium alloy cylinders using a gravimetric method in which unknown uncertainty factors were theoretically determined and subsequently reduced. Molar fractions of the constituents (CO2, Ar, O2, and N2) in the primary standard mixtures were mainly resolved using masses of the respective source gases (CO2, Ar, O2, and N2) that had been filled into the cylinders. To precisely determine the masses of the source gases, the difference in mass of the cylinder before and after filling the respective source gas was calculated by comparison with an almost identical reference cylinder. Although the masses of the cylinders filled with the source gas with respect to the reference cylinder tended to deviate in relation to temperature differences between the source-gas-filled cylinder and surrounding air, the degree of the deviation could be efficiently reduced by measuring the two cylinders at the exact same temperature. The standard uncertainty for the cylinder mass obtained in our weighing system was determined to be 0.82 mg. The standard uncertainties for the O2 molar fractions in the primary standard mixtures ranged from 0.7 to 0.8 µmol mol−1. Based on the primary standard mixtures, the annual average molar fractions of atmospheric O2 and Ar in 2015 at Hateruma island, Japan, were found to be 209339.1±1.1 and 9334.4±0.7 µmol mol−1, respectively. The molar fraction for atmospheric Ar was in agreement with previous reports.